THE GASTRONOMIC IMAGE OF THE TERRITORY: STRUCTURE AND SPECIFICITY - Maria A. Belyaeva (Russian Studies in Culture and Society)
The article is devoted to the gastronomic culture and its derivative – the gastronomic image of the territory. Gastronomy, as a field of knowledge, reveals the connection between food and culture and is an urgent topic of cultural research. Within the framework of this article, the subject of research is the study of the gastronomic image of the territory from a theoretical point of view.